Comparison of Bacterial Healing Performances of Cave Bacteria and Sporosarcina pasteurii in Cement-Based Mortar - Ali, Issam; Canpolat, Orhan; Gungor, Nihal Dogruoz; Yuzer, Nabi; Uysal, Mucteba; Tanyildizi, Harun; Al Hayo, Bashar (Mdpi, 2025)
This research aims to study the bacterial healing process of cement mortar samples exposed to durability effects using bacteria characterized by their ability to precipitate calcium carbonate. Sporosarcina pasteurii is widely used for bacterial healing. This research investigates the performance of S. pasteurii with five types of bacteria isolated from caves (Viridibacillus arenosi, Streptomyces spororaveus, Bacillus zhangzhouensis, Stenotrophomonas rhizophila, and Serratia quinivorans). Cement mortar samples were exposed to high temperatures and freeze-thaw effects to create microcracks. Microcracks were also induced by applying flexural strength loads. Then, the formed microcracks were healed using spraying and injection of the bacterial solution for the first group for 90 days. The control and healed samples were assessed using flexural and compressive strength, water absorption, capillary water absorption, and ultrasonic pulse velocity (UPV) tests. Microstructural analysis was also conducted to evaluate the bacterial healing products. Subsequently, statistical analysis was performed using the results of these tests to compare the various bacterial efficiencies. As a result of the statistical analysis, the total efficiency scores obtained in the statistical analysis were 119 for Stenotrophomonas rhizophila, 112 for Viridibacillus arenosi, and 105 for S. pasteurii. Thus, Stenotrophomonas rhizophila and Viridibacillus arenosi showed the best healing performance compared to the other types of bacteria.
Keywords: bacterial healing; cement mortar; calcium carbonate precipitation; Sporosarcina pasteurii; microcracks